The Progression of Medical Innovations, Challenges, and Implications on Human Health Associated with Nanoparticles (Asian Journal of Pharmaceutics (AJP), 2024)
Nanoparticles (NPs) have emerged as versatile tools in the field of medicine, presenting promising prospectsfor drug delivery and diagnostics. Their distinctive attributes, including a high surface mass ratio and ability totransport substances, facilitate precise drug targeting, minimize toxicity, and enhance therapeutic effects. Despitethese advantages, the rapid progress of nanotechnology in medicine introduces challenges that necessitate rigoroustoxicological assessments to ensure safe application. Researchers are actively bridging the divide between therisks associated with combustion-derived NPs and the potential benefits of engineered NPs in medical contexts.A comprehensive exploration of their impact on the cardiovascular and neurological systems offers insights intotheir behavior and paves the way for responsible practices in nanomedicine. Unlocking the full capabilities ofnanotechnology calls for collaborative endeavors between particle toxicologists and drug delivery specialists,unraveling the intricacies of NP-cell interactions, and revolutionizing drug administration to elevate health-careoutcomes.